Pengaruh Gaya Hidup dan Tingkat Pendapatan terhadap Perilaku Konsumsi Islami pada New Normal (Studi Kasus Masyarakat Muslim Usia Produktif di Surabaya) - Fajirin, Fauzan Bahamarianto; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2021)
In the teachings of Islam, consumption behavior is based on the Al-Quran and Hadith where in consumption, satisfaction is not number one, but maslahah (benefit) must be prioritized in carrying out consumption activities. Many factors can influence Islamic consumption behavior, one of which is lifestyle and income level. Situations and conditions during the "new normal" period can also influence changes in Islamic consumption behavior. The purpose of this research is to see the effect of lifestyle and income levels on Islamic consumption behavior in the new normal. This study uses a quantitative descriptive approach with multiple linear regression data analysis techniques. The results of this study are lifestyle and income levels have a positive effect simultaneously or partially on Islamic consumption behavior in the new normal period.